Underwater dogs - Casteel, Seth. (New York, N.Y. : Little , Brown and Co., 2012)
Casteel got the idea of photographing dogs swimming, working mostly from below to create spooky-adorable images.
Keywords: Casteel, Seth; Dogs -- Pictorial works; Photography of dogs; Underwater photography